Job satisfaction, family functioning and psychological well-being of dual-earner commuter couples in Malaysia - Pai, Farah Syuhada (2018)
Over the last few years, the phenomena of dual-earner commuter couples had gain the attention of the world including Malaysia. The changing of demographic in the workplace had lead some couples to adopt commuting lifestyle in order to remain employed and had given impact towards their psychological well-being. However, a little effort has been given to studying on dual-earner commuter couples psychological well-being and the factors contribute to it, especially in Malaysian context. Various literatures also stated that commuting challenge has negative impacts towards commuter couples. As manifested, the present study was primarily conducted to determine the relationship between job satisfaction, family functioning and psychological well-being of dual-earner commuter couples in Malaysia. A total sample of 180 respondents which consisting of 90 pairs of commuting couples with age range between 23 to 57 years old have been identified using the purposive sampling method. Furthermore, respondents provided data through a structured self-administered questionnaire. The instruments used in this study were the Minnesota Satisfaction Questionnaire Short Form (MSQ-SF) (Weiss, Dawis, England, and Loifquist, 1967), Family Adaptability and Cohesion Evaluation Scale III (FACE-III) (Olson, 1993) and General Health Questionnaire (GHQ- 12) (Goldberg & William, 1998). In addition, the results of this study were analyzed using the Statistical Package for Social Science (SPSS) based on hypotheses that have been constructed to identify a direct correlation between job satisfaction (intrinsic and extrinsic), family functioning (cohesion and adaptability) and psychological well-being. The findings from the analysis of Pearson Product-Moment showed that there were significant negative relationships between job satisfaction (intrinsic and extrinsic) and family functioning (cohesion) with psychological well-being. In contrast, there was also significant positive relationship found between adaptations with psychological well-being of dual- earner commuter couples. In addition, the finding of t-test analysis showed that there were no significant mean differences between husband and wife in work satisfaction (intrinsic and extrinsic), family functioning (cohesion) and psychological well-being. The study also found that only family functioning (adaptation) (β = .20, p < .05) was made a unique contribution to psychological wellbeing. In other word, this association must be interpreted within the commuting context in which that couple’s effort to highly adapt with commuter challenging lifes were more likely effecting their psychological well-being. To sum up, the contribution of the functioning in a family plays an important key factor in shaping and defining the psychological well-being of dual-earner commuter couples.